Maternal regulation of the infant's hypothalamic‐pituitary‐adrenal axis stress response: Seymour 'Gig' Levine's legacy to neuroendocrinology. (11th July 2018) - Suchecki, D.
Abstract : Thirty years ago, Seymour 'Gig' Levine published a serendipitous, yet, seminal finding with respect to the regulatory role of maternal presence on the corticosterone stress response of neonatal rats during the developmental period known as the stress hyporesponsive period. At the same time, his group of students also investigated the stress response of infant monkeys with respect to maternal separation, as a means of understanding the stress to the primary caregiver resulting from disruptions of attachment. Gig and his group of students and collaborators, mainly in the USA and the Netherlands, investigated how initial social relationships buffer the stress response of nonhuman primates and rodent infants. His work in rodents involved determining how prolonged deprivation of maternal care disinhibits the stress response of neonates and how maternal behaviours regulate specific aspects of the hypothalamic‐pituitary‐adrenal axis. Maternal deprivation for 24 hours was useful for determining the importance of nutrition in suppressing the corticosterone stress response, whereas anogenital licking and grooming inhibited stress‐induced adrenocortoctrophic hormone release, with the combination of both behaviours preventing the effects of maternal deprivation on the central hypothalamic stress response. Levine's group also studied the consequences of maternal deprivation on basal and stress‐induced activity of the hypothalamic‐pituitary‐adrenal axis in juveniles and the persistent effects of the replacement of maternal behaviours on these parameters. Gig's legacy allowed many groups around the world to use the 24‐hour maternal deprivation paradigm as an animal model of vulnerability and resilience to stress‐related psychiatric disorders, as well as in studies of the neurobiological underpinnings of disruption of the mother‐infant relationship and loss of parental care, a highly prevalent condition in humans. This review pays homage to a great scientist and mentor, whose discoveries paved the way for the understanding of how early social relationsships build resilience or lead to susceptibility to emotional disorders later in life.